2007
DOI: 10.1038/sj.ijo.0803722
|View full text |Cite
|
Sign up to set email alerts
|

Obese men respond to cognitive but not to catabolic brain insulin signaling

Abstract: Context and objective: Insulin acts in the brain to reduce food intake and body weight and is considered a major adiposity signal in energy homeostasis. In normal-weight men, intranasal insulin administration reduces body fat and improves declarative memory. The present experiments aimed to generalize these findings to obese patients, with a view to evaluate the therapeutic potential of the compound. Design, subjects and measurements: Insulin and placebo, respectively, were intranasally administered four times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
123
1
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(136 citation statements)
references
References 51 publications
7
123
1
5
Order By: Relevance
“…Here, correlational analyses revealed that the effects of insulin on cortical activity were negatively related to the amount of body fat and the degree of peripheral insulin resistance. This outcome contrasts with the fact that, after 8 weeks of intranasal insulin treatment, obese participants displayed preserved susceptibility to the memory-improving effect of insulin [18] in as much as the storage of declarative memory representations also involves neocortical brain areas. However, during i.v.…”
Section: Central Nervous Insulin Resistancecontrasting
confidence: 48%
See 3 more Smart Citations
“…Here, correlational analyses revealed that the effects of insulin on cortical activity were negatively related to the amount of body fat and the degree of peripheral insulin resistance. This outcome contrasts with the fact that, after 8 weeks of intranasal insulin treatment, obese participants displayed preserved susceptibility to the memory-improving effect of insulin [18] in as much as the storage of declarative memory representations also involves neocortical brain areas. However, during i.v.…”
Section: Central Nervous Insulin Resistancecontrasting
confidence: 48%
“…Thus, intranasal administration of neuropeptides to target brain functions might be of particular therapeutic relevance because it bypasses the BBB. However, in pilot experiments in obese men, 8 weeks of intranasal insulin treatment had no effect on body weight and body fat mass [18]. Nevertheless, insulin administration improved declarative memory functions and reduced HPA axis secretory activity, effects that resemble those observed in normal-weight participants [20,25].…”
Section: Central Nervous Insulin Resistancementioning
confidence: 82%
See 2 more Smart Citations
“…In addition to these neural pathways, perivascular pathways, and pathways involving the cerebrospinal fluid (CSF) or nasal lymphatics may play a central role in the distribution of therapeutics from the nasal cavity to the CNS (Thorne et al, 2004). Numerous therapeutics have been delivered to the CNS following intranasal administration and have demonstrated pharmacological effects in animals and in humans (Dhanda et al, 2005), with clinical investigations currently underway for intranasal treatment of Alzheimer's disease (Gozes and Divinski, 2007;Reger et al, 2008) and obesity (Hallschmid et al, 2008).…”
mentioning
confidence: 99%